2022
DOI: 10.1002/esp.5393
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of the soil 137Cs inventory through litter and sediment transport on a hillslope covered by deciduous forest in Fukushima, Japan

Abstract: The long‐term behaviour of radiocaesium (137Cs) activity concentrations in forest ecosystems and their downstream impacts remain important issues in the deciduous broadleaf forests of Fukushima, Japan following the Fukushima Daiichi Nuclear Power Plant accident. To predict 137Cs cycling and discharge in the forest ecosystem, it is important to understand the spatial dynamics of the 137Cs inventory and transport along hillslopes. Therefore, we observed the spatial distribution of the 137Cs inventory and 137Cs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Despite these considerations related to 137 Cs fluxes, the form of 137 Cs is also important, as the litter exported from forests may supply radioactive materials that are more bioavailable than those transported with mineral particles to downstream rivers and lakes ( 43 46 ). This was not incorporated in the current model version and could be included in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these considerations related to 137 Cs fluxes, the form of 137 Cs is also important, as the litter exported from forests may supply radioactive materials that are more bioavailable than those transported with mineral particles to downstream rivers and lakes ( 43 46 ). This was not incorporated in the current model version and could be included in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach relied on the use of a mass balance model to map the spatial distribution of 137 Cs inventories and quantify 137 Cs transport via sediment and litter in 2016-2017 along a deciduous forested hillslope of Date, in 480 the Fukushima Prefecture (Oda et al, 2022). They showed that 137 Cs inventories were significantly higher in downslope riparian areas (455 kBq m -2 ) than in the upslope ridge area (179 kBq m -2 ).…”
mentioning
confidence: 99%